Effect of preparation conditions and Co–Pi groups as a noble metal-free redox mediator and hole extractor to boost the photoelectrochemical water oxidation for 1D nanorod α-Fe2O3. (7th December 2021) - Qin, Ai; Fang, Wanqing; Lin, Yimin; Xv, Rongzi; Fu, Li
Abstract : Co–Pi groups have a double effect on the short nanorod α-Fe2 O3 photoanode: accelerating the hole separation and improving the water oxidation kinetics. Abstract : Photoelectrochemical water splitting for hydrogen production is an ideal method for solar energy utilization. Herein, α-Fe2 O3 was prepared by a hydrothermal process and the precursor concentration, calcination temperature and hydrothermal time were optimized. The Co–Pi groups were deposited on the surface by two-step dipping process. The preparation conditions and loading capacity of CoPi were optimized. SEM showed that the morphology of α-Fe2 O3 was short nanorods. XPS indicated that CoPi was successfully deposited on the surface of Fe2 O3 . TEM and XRD showed that CoPi was amorphous. The photocurrent density of Fe2 O3 /CoPi increased to 1.95 mA cm −2 at 1.23 VRHE, which was 1.91 times that of bare Fe2 O3 . After CoPi modification, the initial potential shifted negatively by 70 mV. It could be inferred that CoPi acted as an effective water oxidation co-catalyst to reduce the activation energy of the oxygen evolution reaction. The chopping I – t curve showed that the transient anodic spike of Fe2 O3 decreased after CoPi deposition. This indicated that CoPi acted as a hole extractor and redox mediator to reduce the charge accumulation on the Fe2 O3 surface. Through calculation, the ABPE of Fe2 O3 /Co–Pi was 2.1 times that of Fe2 O3 . The charge injection efficiency of Fe2 O3 /Co–Pi at 1.23 VRHE was 1.6 times that of Fe2 O3 . This study presented a richer understanding on the functions and promotional effects of the preparation conditions and CoPi groups for Fe2 O3 photoanodes.